Thrombospondin-1 induces immunogenic cell death in human mucoepidermoid carcinoma MC-3 cells via the PERK/eIF2α signaling pathway: potential implications for tumor immunotherapy - Yixuan Zhu; Kaizhi Cai; Lijuan Guo; Huan Zhang; Li Guan; Zongyao Zhang; Pengcheng Huang; Sen Yang (Discover Oncology)
Abstract Objective To investigate whether Thrombospondin-1 (TSP-1) induces immunogenic cell death (ICD) in human mucoepidermoid carcinoma (MC-3) cells and explore its potential to induce calreticulin (CRT) exposure via the PERK/eIF2α signaling pathway. Methods The MC-3 cell line was used as the research model. The CCK-8 assay was performed to determine the optimal seeding density, TSP-1 concentration, and treatment time. Annexin V/PI double staining combined with flow cytometry was used to assess apoptosis across different experimental groups (blank control, TSP-1, paclitaxel (PTX), TSP-1 + PTX). Cells were divided into groups: blank control, PTX, TSP-1, TSP-1 + ISRIB (ISRIB: Integrated Stress Response Inhibitor), and TSP-1 + PTX, and CRT expression was detected by flow cytometry. Immunofluorescence, Western blot, and qPCR were used to detect the expression of PERK (Protein Kinase R-like Endoplasmic Reticulum Kinase), eIF2α (eukaryotic Initiation Factor 2α), and CRT. All experiments were performed in triplicate, and data were analyzed using GraphPad Prism 8.0 software. Statistical significance was set at P < 0.05. Results At a seeding density of 2 × 104/mL, MC-3 cells reached the growth plateau by day six. The optimal concentration and duration of TSP-1 treatment were 0.1 μmol/L and 72 h, respectively. Flow cytometry, immunofluorescence, Western blot, and qPCR results revealed that TSP-1 significantly induced CRT exposure in MC-3 cells (P < 0.05), accompanied by the upregulation of PERK and eIF2α expression (P < 0.05). Co-treatment with PTX further enhanced these effects, while the addition of ISRIB reduced the expression of PERK, eIF2α, and CRT (P < 0.05). Conclusion TSP-1 induces ICD in MC-3 cells, accompanied by CRT exposure, potentially mediated through the activation of the PERK/eIF2α signaling pathway. These findings suggest that TSP-1 may have potential as an adjunct to chemotherapy for enhancing tumor immunotherapy.